Economic burden of antimicrobial resistance on patients in Pakistan - Safdar, Numrah; Saleem, Saad; Salman, Muhammad; Tareq, Ahmad Hussen; Ishaq, Sidra; Ambreen, Saadia; Hameed, Abdul; Habib, Muhammad Bilal; Ali, Tariq Mahmood (Frontiers in Public Health, 2025)
BackgroundAntimicrobial resistance (AMR) occurs when microbes undergo changes that render antimicrobial drugs ineffective against them, resulting in limited, more expensive treatment options, longer hospital stays, and increased mortality rates. No study has estimated the costs related to AMR in hospitals in Pakistan. This study was conducted to determine the financial burden of antimicrobial resistance (AMR) in Pakistan and to compare it with the additional costs incurred by patients who respond well to antimicrobial treatments. The study also aimed to identify the most frequent types of microbes that cause bloodstream infections in Pakistan.MethodsThis quantitative study was conducted employing a prospective cohort study design. A sample of 193 patients was selected from two public sector tertiary care hospitals in the twin cities of Islamabad and Rawalpindi for a period of 7 months. The frequency trends of antimicrobial resistance against 12 blood pathogens were determined by analyzing culture sensitivity reports from patients who tested positive, as provided by pathology laboratories of the study hospitals. Direct and indirect costs were calculated using data from patients’ medical records and through direct interactions with patients.ResultsThis study estimated that treating cases of AMR resulted in approximately USD 33.97 [Pakistani Rupees (PKR) 9483.2] in additional costs compared to treating susceptible infections due to extended lengths of hospital stays. However, indirect costs such as spending on food, productivity loss, and accommodation are USD 55.84 (PKR 15588.3) higher in the non-infected control cohort compared to the cases. Direct costs (transport, pharmacy, and laboratory expenses) are directly related to AMR and add an additional burden of USD 12.30 (PKR 3435) for cases compared to non-infected controls. In comparison to susceptible controls, cases incur an additional cost of USD 32.9 (PKR 9185.9).ConclusionThis study helped predict the economic burden of antimicrobial resistance in admitted patients with bloodstream infections (BSIs) in low- and middle-income countries, such as Pakistan, by different variable cost estimates. These findings will help in designing the most appropriate approach to combat AMR. Additionally, this study serves as a baseline tool that can be extrapolated to estimate the national economic burden because of AMR.